ANALYSIS OF FACTORS AFFECTING PRODUCTION AND REVENUE OF TUBEROSE (Polianthes tuberosa L.) FARMERS IN PRODUCTION CENTER OF CENTRAL JAWA - Ani Mulyani; Titik Ekowati; Endang Dwi Purbajanti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The purpose of this research is to analysis the effect of using production factors, farmer income and feasibility on Tuberoses flower (Polianthes tuberosa L.) crops. Research used census method and the number of sampel are 30 respondents, in Semarang and Magelang regency. Analysis of research used  Cobb-douglas model of production function,  linier regression function and one sample t test.The results of the   analysis of production function showed the amount of seeds, organic fertilizer,  NPK fertilizer, labor and the water have significant effect. The results of the analysis of the income function that have significant effect were the price and the amount of production,  this means, if increase in prices or increase in production, the farmer's income will increase. One samplet t-test results showed tuberose flowers farming was profitable and feasible to be developed